Effect of pomegranate on metabolic indices and inflammatory biomarkers in streptozocotocin-nicotinamide induced diabetic rats - Rouhi, Seyedeh Zeinab Taheri (2015)
Type 2 Diabetes Mellitus (T2DM) is a persistent health and lifestyle difficulty in affluent societies worldwide. T2DM is associated not only with hyperinsulinaemia and hyperglycemia, but also with other disorders such as atherosclerosis,hypertension, inflammatory disorders and abnormal lipid profile. Fruits have been applied universally in the treatment of these side effects, since they are natural,safe, and available. The therapeutic potential of pomegranate sections has been stated by multitudinous scientists using various in vitro assays, which is through the attendance of particular bioactive compounds. The present study aimed to determine the effect of pomegranate juice (PJ) and pomegranate seed (PS) consumption, and their potential effect on treatment of diabetes and its associated complications such as abnormalities in plasma glucose, insulin, inflammatory factors, lipid profile, and pancreatic islets of Langerhans in T2D rats. Moreover,the identification of the bioactive compounds and antioxidant activity of PJ and PS were studied. Accordingly forty (n= 40) adult healthy male Sprague Dawley rats,were randomly divided into five groups of control (diabetic and non –diabetic) and experimental (diabetic), and T2DM was induced in four groups by administration of streptozotocin-nicotinamide; As they received one intraperitioneal injection of 60 mg/kg b.w of streptozotocin (STZ) each. The dose of 120 mg/kg b.w i.p nicotinamide (NAD) was administered 15 min before STZ. Diabetic animals in PJ,PS , and glibenclamide treated groups (n=8 each) received 1 ml of PJ, 100 mg PS powder diluted in 1 ml of distilled water, and 5 mg/ kg b.w respectively, every day for 21 days through oral gavage. Rats in all groups were sacrificed on day 22. The obtained data was analyzed by SPSS software (v: 20) using One-way analysis of variance (ANOVA). The outputs demonstrated that PJ and PS treatment had slight reducing effect on plasma glucose concentration, with no statistically significant difference comparing to diabetic control (DC) group (P>0.05). Moreover, no impact on plasma insulin was observed. While PS treatment did not show any considerable changes in the size and number of islets of Langerhans, PJ treated group showed significant repair and restoration signs of islets of Langerhans (P<0.05). The outputs demonstrated that PJ administration lowered the parameters of plasma total cholesterol and triglyceride significantly, and LDL-c non-significantly less than those of DC group; In contrast, PS treatment significantly raised plasma total cholesterol, LDL-c, and HDL-c levels compared to the DC rats (P<0.05). PJ and PS significantly reduced the levels of plasma inflammatory biomarkers, which were actively raised in T2D rats (P<0.05). Although further studies should investigate the biochemical mechanisms underlying PS activities as future research plans, the present data suggests that PJ has a protective effect against lipid abnormalities and overexpression of inflammatory cytokines as diabetes side effects. High antioxidant flavonoids and polyphenolic active constituents present in PJ are possibly responsible for its antihyperlipidemic and anti-inflammatory effect, as well as the restoration effect on the ,damaged islet cells of Langerhans in experimental rats. Hence, the pharmacological, biochemical, and histopathological profiles of PJ treated rats obviously indicated its helpful effects in amelioration of diabetes-associated complications, which can help to management of diabetes.